2018
DOI: 10.1093/tas/txx005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health challenges on pig growth performance, carcass characteristics, and net returns under commercial conditions

Abstract: Understanding how disease affects commercial production is imperative for pig producers to quantify its full impact on pig performance, carcass quality, and net returns. The objective of this experiment was to assess the productivity and economic importance of naturally occurring health challenges (HC) under commercial conditions. Three 1,000 pig grow-finish facilities received 936 pigs each. The experimental period started approximately 34 d post placement at an average start BW of 13.1 ± 0.2 kg. Barns were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
2
34
1
Order By: Relevance
“…On the other hand, a worsening in performance as the size of the herd increases has been reported previously. In a study analysing production parameters and production cost over time (2010-2014) in Spain, Rocadembosch et al [39] concluded that herd size affected negatively most performance indicators, including ADG in nursery and nishing stages, as also found in this other study [40].…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, a worsening in performance as the size of the herd increases has been reported previously. In a study analysing production parameters and production cost over time (2010-2014) in Spain, Rocadembosch et al [39] concluded that herd size affected negatively most performance indicators, including ADG in nursery and nishing stages, as also found in this other study [40].…”
Section: Discussionsupporting
confidence: 72%
“…Pathogenic E. coli strains are common agents causing a variety of intestinal disorders in neonatal and weaning piglets, which may be followed by terminal septicaemia, an important cause of economic loss for swine producers (Lee et al, 2008). Other bacteria involved in farm infections are S. aureus, which increases mortality in farms (Osadebe et al, 2013), furthermore, other pathogens like Mycoplasma hyopenumoniare or reproductive and respiratory syndrome virus (PRRSV) contribute to respiratory disease and impact significantly in economic losses to the swine industry (Cornelison et al, 2018;Helme et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2 ( USDA, 2016 ). Mortality has been shown to be significantly greater in animals experiencing a high health challenge [porcine reproductive and respiratory syndrome virus (PRRSV) and swine influenza virus A (IAV); 19.9%)] compared to moderate health challenge (IAV; 7.7%) or low health challenge (no PRRSV or IAV; 3.3%; Cornelison et al, 2018 ). Such data illustrates the significant impact that the combination of infectious causes of mortality can have on postweaning mortality.…”
Section: Resultsmentioning
confidence: 99%